Systems and synthetic biology-driven engineering of live bacterial therapeutics - Kim, Kangsan; Kang, Minjeong; Cho, Byung-Kwan (Frontiers in Bioengineering and Biotechnology, 2023)
The past decade has seen growing interest in bacterial engineering for therapeutically relevant applications. While early efforts focused on repurposing genetically tractable model strains, such as Escherichia coli, engineering gut commensals is gaining traction owing to their innate capacity to survive and stably propagate in the intestine for an extended duration. Although limited genetic tractability has been a major roadblock, recent advances in systems and synthetic biology have unlocked our ability to effectively harness native gut commensals for therapeutic and diagnostic purposes, ranging from the rational design of synthetic microbial consortia to the construction of synthetic cells that execute 'sense-and-respond' logic operations that allow real-time detection and therapeutic payload delivery in response to specific signals in the intestine. In this review, we outline Engineering live microbial therapeutics 2 the current progress and latest updates on microbial therapeutics, with particular emphasis on gut commensal engineering driven by synthetic biology and systems understanding of their molecular phenotypes. Finally, the challenges and prospects of engineering gut commensals for therapeutic applications are discussed.